2023
DOI: 10.1039/d2dt03868d
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant effects on electrochemically durable lead halide perovskite electro-catalysts

Abstract: Electrochemical-durable perovskite electrodes of nickel foam/TiO2/FA(Pb1-xGex)I3, passivated by various surfactants of tetra-n-alkyl ammonium halide (alkyl= ethyl, butyl, hexyl, or octyl; halide= I, I0.5Br0.5, Br, Br0.5Cl0.5, or Cl), were successfully applied...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…Generally speaking, all solids have a prominent peak at 529.0 eV due to the lattice oxygen from metals bonded to the oxygen atoms while another one with less intensity at 531.0 eV from the oxygen vacancies. Since similar results have been reported for niobates and perovkites, 9,56,60 it can be concluded that CuNb is the sole sample with these features. Two other emission lines for O 1 s appears for the ZnNb, PbNb and LaFeMn with lower intensity at 530.3–532.0 and 533.2 eV, which is likely due to the adsorbed oxygen (O ads ) and adsorbed water molecules, and carbonates.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Generally speaking, all solids have a prominent peak at 529.0 eV due to the lattice oxygen from metals bonded to the oxygen atoms while another one with less intensity at 531.0 eV from the oxygen vacancies. Since similar results have been reported for niobates and perovkites, 9,56,60 it can be concluded that CuNb is the sole sample with these features. Two other emission lines for O 1 s appears for the ZnNb, PbNb and LaFeMn with lower intensity at 530.3–532.0 and 533.2 eV, which is likely due to the adsorbed oxygen (O ads ) and adsorbed water molecules, and carbonates.…”
Section: Resultssupporting
confidence: 81%
“…8 In particular, perovskites have unique physicochemical properties, and applications in electronics, optics, catalysis, medicine and magnetism are actively sought. 9,10 Of the various types of perovskites, double-perovskite materials are most commonly used for solar cells due to their tunable band gaps and effective electron and hole carrier mass, with their own advantages and disadvantages. 10 Another interesting property of double-perovskites is their variability in composition.…”
Section: Introductionmentioning
confidence: 99%
“…For the pristine perovskite film, characteristic peaks appeared at 14.8°, 20.7°, 25.3°, 29.1°, 32.6°, 35.8°, 41.4°, and 43.9°, corresponding to (110), (112), (202), (220), (310), (312), (224), and (314) crystal planes, respectively. 35–38 The XRD pattern of the perovskite film with poly-TPD displayed characteristic diffraction peaks that were almost identical to those of the pristine perovskite film, indicating that the crystal structure of the perovskite was not significantly altered by the introduction of poly-TPD. However, the relative intensity of the characteristic diffraction peaks in the perovskite films was enhanced by the introduction of poly-TPD, suggesting an improvement in the integrity of the triple-cation perovskite crystal film.…”
Section: Resultsmentioning
confidence: 94%